ANALISIS PENGELOLAAN DANA BANTUAN LANGSUNG TUNAI (BLT) DALAM PENCAPAIAN EFEKTIVITAS DANA PROGRAM KOMPENSASI PENGURANGAN SUBSIDI BAHAN BAKAR MINYAK (PKPS-BBM) DI KECAMATAN RANTAU SELATAN KABUPATEN LABUHANBATU - Irwadana Juliandri Nadeak (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
The research aims at analyzing the Direct Cash Grant (BLT) Management in Achieving the Fund Effectiveness of Fuel Subsidy Reduction Compensation Program (PKPS BBM) at Kecamatan Rantau Selatan, Labuhan Batu District. The research variables comprise two variables. The first variable is the Direct Cash Grant Management consisting of sub-variables: planning, organizing and controlling. The indicators are data collection, socialization, distribution and control. The second variable is Fund Effectiveness of Fuel Subsidy Reduction Compensation Program (PKPS BBM) with the indicators: right target, timeliness, and advantages. The research result shows that the Direct Cash Grant (BLT) Management in Achieving the Fund Effectiveness of Fuel Subsidy Reduction Compensation Program (PKPS BBM) still encounters four main obstacles. First, insufficiently allocated time has caused data collection and trainings for the data collectors not optimally conducted and demographically unwell-distributed.Second, the indicators of poor family can not be applicable for all areas. Third, lacking coordination among institutions has resulted in insufficient control. Fourth, the effectiveness of BLT PKPS BBM fund at Kecamatan Rantau Selatan, Labuhan Batu District has yet to be achieved in the terms of the right target, timeliness, and advantages.